Obesity and Natriuretic Peptides, BNP and NT-proBNP: Mechanisms and Diagnostic Implications for Heart Failure - Madamanchi, Chaitanya (2014)
Many advances have been made in the diagnosis and management of heart failure (HF) in recent years. Cardiac biomarkers are an essential tool for clinicians: point of care B-Type Natriuretic Peptide (BNP) and its N-terminal counterpart (NT-proBNP) levels help distinguish cardiac from non-cardiac causes of dyspnea and are also useful in the prognosis and monitoring of the efficacy of therapy. One of the major limitations of HF biomarkers is in obese patients where the relationship between BNP and NT-proBNP levels and myocardial stiffness is complex. Recent data suggest an inverse relationship between BNP and NT-proBNP levels and body mass index. Given the ever-increasing prevalence of obesity world-wide, it is important to understand the benefits and limitations of HF biomarkers in this population. This review will explore the biology, physiology, and pathophysiology of these peptides and the cardiac endocrine paradox in HF. We also examine the clinical evidence, mechanisms, and plausible biological explanations for the discord between BNP levels and HF in obese patients.